The Dynamics of Macroeconomic and Microeconomic Determinants with The Capital of Rural Banks - Ponziani, Regi Muzio (JEJAK: Jurnal Ekonomi dan Kebijakan, 2022)
The research aims to investigate the dynamics among rural banks’ capital, macroeconomic variables and microconomic variables. Macroeoconomic variable consists of infllation and interest. Microeconomic variables consist of loan to deposi ratio, nonperforming loans, and return on assets. The data are excerpted from OJK and BI’s website. The data are monthly data extending from January 2010 until May 2021. The testing method used is vector error correction model (VECM). The results show that rural banks’ capital is significantly affected the previous state of capital and profitability. This indicates the importance of sustainability of capital in rural banks and how it is very much dependent upon the profitability of the rural banks. Further, the research results show that there ar two cointegrating functions in the model. Both cointegration functions are influential to inflation. The speed adjustment derived from the residuals of capital function is 0.6754% and 13.5669% for residual from inflation function itself. The slow adjustment process is due to the small market share and assets of rural banking sector. In addition, capital, nonperforming loans, and return on assets are pivotal for central bank monetary policy to control inflation.